Behind the curtain: therapeutic drug monitoring of psychotropic drugs from a laboratory analytical perspective - Scherf-Clavel, Maike; Baumann, Pierre; Hart, Xenia Marlene; Schneider, Heike; Schoretsanitis, Georgios; Steimer, Werner; Zernig, Gerald; Zurek, Gabriela (Therapeutic drug monitoring, 2024)
Purpose: - Therapeutic drug monitoring (TDM) is a well-established tool for guiding psychopharmacotherapy and improving patient care. Despite their established roles in the prescription of psychotropic drugs, the “behind the curtain” processes of TDM requests are invariably obscure to clinicians, and literature addressing this topic is scarce. - Methods: - In the present narrative review, we provide a comprehensive overview of the various steps, starting from requesting TDM to interpreting TDM findings, in routine clinical practice. Our goal was to improve clinicians' insights into the numerous factors that may explain the variations in TDM findings due to methodological issues. - Results: - We discussed challenges throughout the TDM process, starting from the analyte and its major variation forms, through sampling procedures and pre-analytical conditions, time of blood sampling, sample matrices, and collection tubes, to analytical methods, their advantages and shortcomings, and the applied quality procedures. Additionally, we critically reviewed the current and future advances in the TDM of psychotropic drugs. - Conclusions: -The “behind the curtain” processes enabling TDM involve a multidisciplinary team, which faces numerous challenges in clinical routine. A better understanding of these processes will allow clinicians to join the efforts for achieving higher-quality TDM findings, which will in turn improve treatment effectiveness and safety outcomes of psychotropic agents.